On the status of Newtonian gravitational radiation - Linnemann, N; Read, J (Springer Nature, 2021)
We discuss the status of gravitational radiation in Newtonian theories. In order to do so, we (i) consider various options for interpreting the Poisson equation as encoding propagating solutions, (ii) reflect on the extent to which limit considerations from general relativity can shed light on the Poisson equation’s conceptual status, and (iii) discuss various senses in which the Poisson equation counts as a (non-)dynamical equation.